Superior Li-ion storage of VS4 nanowires anchored on reduced graphene - Yang, Guang (2021)
Research on VS4 is lagging due to the difficulty in its tailored synthesis. Herein, unique architecture design of one-dimensional VS4 nanowires anchored on reduced graphene oxide is demonstrated via a facile solvothermal synthesis. Different amounts of reduced graphene oxide with VS4 are synthesized and compared regarding their rate capability and cycling stability. Among them, VS4 nanowires@15 wt% reduced graphene oxide present the best electrochemical performance. The superior performance is attributed to the optimal amount of reduced graphene oxide and one-dimensional VS4 nanowires based on (i) the large surface area that could accommodate volume changes, (ii) enhanced accessibility of the electrolyte, and (iii) improvement in electrical conductivity. In addition, kinetic parameters derived from electrochemical impedance spectroscopy spectra and sweep rate dependent cyclic voltammetry curves such as charge transfer resistances and Li+ ion apparent diffusion coefficients both support this claim. The diffusion coefficient is calculated to be 1.694 × 10-12 cm2 s-1 for VS4 nanowires/15 wt% reduced graphene oxide, highest among all samples.